Learner autonomy in an online project-based learning: voices from Indonesian EFL students - Chakim, Nur; Widiati, Utami; Prayogo, Johannes Ananto; Romadhon , Adi Sasongko (Universitas Muhammadiyah Sidoarjo, 2026)
This study explored university students' levels of autonomy and identified the challenges they face in becoming more autonomous learners within a university context. The research involved 80 students from a public university in Surabaya, East Java, Indonesia. A mixed-methods sequential explanatory design was employed, comprising two phases: a survey phase and an interview phase. The data were collected using closed-ended questionnaires to assess students’ levels of autonomy and semi-structured interviews to examine the challenges hindering students’ autonomy. Next, the quantitative data from the questionnaire were analyzed using simple statistical techniques, including percentages and mean scores, while the qualitative data were analyzed using thematic analysis. The findings revealed two key results. First, students showed high levels of autonomy across all dimensions—technical, psychological, political, and socio-cultural. Notably, none of the questionnaire items indicated a low level of autonomy. Students attributed their high autonomy to the flexibility of working independently at home and leveraging internet resources to complete their projects. They also displayed strong sociability, adaptability, and collaboration skills in achieving their goals. Second, the primary challenges faced by students to be more autonomous in online meetings involved: lecturers’ compulsory instructions, low motivation, lack of discipline, poor time management, dependence on lecturers, lack of skills, and limited interaction.